Plant - "Burnie, David" (Dorling Kindersley: London, 1989)
This title is a valuable resource for students learning about all aspects of plants from how the wind can affect a plant's shape to the different stages of germination. Discover amazing facts - the earliest 'plants' were so small it would have taken dozens of them to cover a pinhead
Keywords: Science - Book